Stability of LaNi5-xSnx cycled in hydrogen - Borzone, Emiliano Manque (2014)
In this work we study the effect of cycling in hydrogen with a purity grade 4.5 of six alloys belonging to the LaNi5-xSnx family for 0 ≤ x ≤ 0.5. Measurements consist in the alternate repetition of absorption reactions at a temperature of 316 K and an initial pressure of 800 kPa, each followed by a desorption reaction at the same temperature and a maximum backpressure of 2 kPa. All samples present good stability, preserving at least 98% of their initial capacity after 100 cycles. Samples with composition LaNi5 and LaNi4.55Sn0.45 were subjected to 1000 cycles, after which we observe a higher stability from the Sn-containing alloy (96% of the initial capacity preserved versus 92% for LaNi5). Absorption characteristic times do not suffer important changes in either case. Desorption is gradually retarded when Sn content is higher than 0.4 at.